Safe and effective grinding - Skills Education Australia Pty. Ltd.; Safetycare Australia Pty. Ltd. (Australia : Skills education Australia, 1991)
This video discusses the workers safety during working hours and its focussed on grinding machinery industry
VCD format
Keywords: Industrial safety; Grinding machinery industry; Grinding and polishing